Pembelajaran Kreatif Untuk Mewujudkan Anak-Anak Yang Cerdas, Kreatif, dan Berkarakter - Heru Kurniawan (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: Creative learning is learning that rets on four basic foundation, namely learning fun designed for children; learn to be more than getting a good value, but is to produce work in the form of learning: intellectual, creative permormance, and educational activities; learning always appreciated the value and the publication of the teacher; and learning that can improve the child's motivation to learn. With four foundsations above, this creative learning will be formed: children are intellegent, that who could resolve the issue of learning in accordance with the breadth of his knowledge; a creative child, the child can actualize ideas and feelings in concrete; and children who have personality and good character in their daily lives. Keywords creative learning, intellegent, creative, characters